2011
DOI: 10.3844/ajessp.2011.377.382
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Bio-Fuel Blends and Fuel Injection Pressure on Diesel Engine Emission for Sustainable Environment

Abstract: Problem statement: Diesel engine emits more pollutants to atmosphere causing air pollution. This necessitates the search of a renewable alternate fuel which is environment friendly. The objective of this research was to investigate the environmental aspects of pongamia bio-fuel in a single cylinder diesel engine with the influence of fuel injection pressure. Approach: Bio-fuel was prepared from non-edible Pongamia pinnata oil by transesterification and used as a fuel in C.I engine. The effect of fuel injection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Meanwhile, a blend of diesel fuel, bioethanol, and sunflower methyl ester serves as a diesel engines fuel, the proportion of CO content in emissions drops as the proportion of bioethanol in the blends increases. Muralidharan. K et al(2011) showed that whenever biodiesel made from pongamiapinnata oil by transesterification is utilized in a C. I engine, blend B5 exhibits decreased engine emissions of unburnt hydrocarbon, carbon monoxide, oxides of nitrogen, and carbon dioxide at full load [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Meanwhile, a blend of diesel fuel, bioethanol, and sunflower methyl ester serves as a diesel engines fuel, the proportion of CO content in emissions drops as the proportion of bioethanol in the blends increases. Muralidharan. K et al(2011) showed that whenever biodiesel made from pongamiapinnata oil by transesterification is utilized in a C. I engine, blend B5 exhibits decreased engine emissions of unburnt hydrocarbon, carbon monoxide, oxides of nitrogen, and carbon dioxide at full load [11].…”
Section: Introductionmentioning
confidence: 99%
“…According to Lawrence et al (2011), utilising prickly poppy methyl ester combined with diesel in a diesel engine boosted brake thermal performance and output while decreasing specific fuel usage. The pattern seen is because bioethanol has fewer carbon particles than diesel [13]. When contrasted with petroleum diesel, biodiesel lessens CO and HC emissions owing to its high oxygen proportion and lower carbon-to-hydrogen concentration.…”
Section: Introductionmentioning
confidence: 99%
“…The new type of biodiesel is prepared from non-edible pongamia pinnata oil by transesterification and used as a fuel in C.I engine. The authors reported that blend B5 exhibits lower engine emissions of unburnt hydrocarbon, carbon monoxide, oxides of nitrogen and carbon dioxide at full load [8]. The experiments were performed in a single cylinder DI diesel engine fueled with a blend of pungam methyl ester for the proportion of PME10, PME20and PME30 by volume with diesel fuel for validation of simulated results.…”
Section: Introductionmentioning
confidence: 99%
“…The scientists are confronted with the following new challenges; they are related with environmental hazards, fuel scarcity, energy demand and stringent emission norms. The above difficulties can easily be overcome by discovering more environmental friendly oxygenated fuels such as ethanol (Muralidharan and Govindarajan, 2011;Rajkumar and Govindarajan, 2011;Chockalingam et al, 2010).…”
Section: Introductionmentioning
confidence: 99%